THE IMPACT OF ICT SECTOR ON THE SOCIAL PILLAR OF SUSTAINABLE DEVELOPMENT - TEODORESCU ANA-MARIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2016)
The human being is the main axis in setting sustainable development goals. Sustainable development, through its components - economic and environmental, has only one beneficiary - the human factor who benefits of income, education, good quality environmental factors, and enjoy inter and intra-generational equity. Information technology and communications contributes to fulffiling the goals of sustainable development through access to information society services (e-health, e-government, e-learning), access to education. This article presents the sustainable development objectives and the impact of ICT sector on the social pillar of sustainable development. I used a theoretical research and qualitative analysis of the data. I presented values indicators at the european level, the lowest and highest value, and recorded values for Romania.